2011
DOI: 10.1177/0009922810394838
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Streptococcal Pharyngitis With Once-Daily Amoxicillin Versus Intramuscular Benzathine Penicillin G in Low-Resource Settings: A Randomized Controlled Trial

Abstract: Background: Primary prevention of acute rheumatic fever is achieved by proper antibiotic treatment of group A β-hemolytic streptococcal (GAS) pharyngitis. Methods: To assess noninferiority of oral amoxicillin to intramuscular benzathine penicillin G (IM BPG). Children (2 to 12 years) meeting enrollment criteria were randomized 1:1 to receive antibiotic treatment in 2 urban outpatient clinics in Egypt and Croatia. Results: A total of 558 children (Croatia = 166, Egypt = 392) were randomized, with 368 evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
7
0
2
Order By: Relevance
“…A previous study by Rimoin et al (2011) found that oral amoxicillin treatment was inferior to IM penicillin treatment in Egyptian children with poor compliance of (30.1%), and of comparable efficacy in Croatian children of good compliance (84.4%), suggesting IM BPG should be preferred where compliance is a major concern [49]. However in our study, compliance was not an issue with treatment regimens, as parents/guardians of children in the amoxicillin group were strongly stressed on the importance of administering the antibiotic at the same time every day for 10 days each month.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…A previous study by Rimoin et al (2011) found that oral amoxicillin treatment was inferior to IM penicillin treatment in Egyptian children with poor compliance of (30.1%), and of comparable efficacy in Croatian children of good compliance (84.4%), suggesting IM BPG should be preferred where compliance is a major concern [49]. However in our study, compliance was not an issue with treatment regimens, as parents/guardians of children in the amoxicillin group were strongly stressed on the importance of administering the antibiotic at the same time every day for 10 days each month.…”
Section: Discussionmentioning
confidence: 88%
“…However, even if the oral therapy seems to be the preferable choice, the major driver of its success remains proper compliance, where several studies have correlated treatment failures to non-adherent patients [49].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with injectable antibiotics, oral antibiotics are associated with fewer complications, less severe hypersensitivity reactions, and no pain at the injection site; however, drug compliance may be a problem [ 12 60 ]. Therefore, IM benzathine penicillin G may be used for patients deemed to have difficulty complying with a 10-day oral antibiotic regimen [ 12 60 61 ]. Studies have found no significant differences in the clinical efficacy of 10-day amoxicillin oral antibiotic therapy and single IM injection of benzathine penicillin G [ 61 62 ].…”
Section: Recommendationsmentioning
confidence: 99%
“…Therefore, IM benzathine penicillin G may be used for patients deemed to have difficulty complying with a 10-day oral antibiotic regimen [ 12 60 61 ]. Studies have found no significant differences in the clinical efficacy of 10-day amoxicillin oral antibiotic therapy and single IM injection of benzathine penicillin G [ 61 62 ].…”
Section: Recommendationsmentioning
confidence: 99%
“…Many studies have shown that amoxicillin taken once a day may be as effective as oral penicillin V. There had been trials about once-daily therapy for strep throat with amoxicillin. [6][7][8] We aimed to compare efficacy of once-daily orally amoxicillin and BPG in relieving various clinical manifestations and their bacteriologic response to the pharyngitis.…”
Section: Introductionmentioning
confidence: 99%